2009
DOI: 10.1177/0148558x0902400107
|View full text |Cite
|
Sign up to set email alerts
|

Do Auditors Price Audit Committee's Expertise? The Case of Accounting versus Nonaccounting Financial Experts

Abstract: The issue of whether audit pricing reflects the effectiveness of the audit committee is of fundamental interest to auditors, managers, and others. Auditors are expected to price the effectiveness of the audit committee because it relates to the control risk and thus, the overall audit risk. This study examines the relation between audit fees and a key determinant of the audit committee's effectiveness—that is, the financial expertise of the audit committee. Though the Sarbanes-Oxley Act mandates the disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 41 publications
11
100
0
3
Order By: Relevance
“…On the other hand, in model (4), the financial expert variable (FINEXP) is negative and significant. This finding indicates that audit fees are lower for those companies who have a financial expert on their board, similar to the finding of Krishnan and Visvanathan (2009).…”
Section: Resultssupporting
confidence: 78%
“…On the other hand, in model (4), the financial expert variable (FINEXP) is negative and significant. This finding indicates that audit fees are lower for those companies who have a financial expert on their board, similar to the finding of Krishnan and Visvanathan (2009).…”
Section: Resultssupporting
confidence: 78%
“…Board and audit committee members with corporate or financial backgrounds are associated with firms that have smaller discretionary current accruals (Xie, Davidson, and DaDalt 2003). However, Krishnan and Visvanathan (2009) find no significant relationship between non-accounting financial expertise and audit fees, suggesting that auditors perceive that only accounting financial expertise contributes to the effectiveness of the audit committee.…”
Section: Proposition Developmentmentioning
confidence: 82%
“…On the one hand, some studies have found that corporate governance is associated with lower audit fees (e.g. Griffin, Lont, and Sunb 2008;Krishnan and Visvanathan 2009). This result may be due to external auditors perceiving that better corporate governance is associated with stronger internal controls and lower risk of financial misreporting.…”
Section: Proposition Developmentmentioning
confidence: 99%
See 2 more Smart Citations